Development and quality assessment of Coalho cheese using indigenous Pakistani milk sources: Nili-Ravi buffalo and Kamori goat - Wahab Ali Khan; Iqra Yasmin; Syed Abdul Wadood; Abbas Khan; Aiza Qamar; Maryam Hameeda; Fatima Farooq Ali; Khunsha Qamar Khan (Discover Food)
Abstract The milk compositional values of two indigenous breeds of Pakistan, i.e., Nili-Ravi buffalo and Kamori goat, were evaluated along with fatty acid profile (FAME) through GM-MS. Coalho cheese samples were evaluated for physicochemical, sensory and rheological characteristics over 30 days’ storage with data being analyzed by ANOVA and Principal Component Analysis. The results exhibited significant compositional variations among milk types, in which buffalo milk demonstrated higher fat and protein content compared to goat milk, which contains more unsaturated fatty acids and mineral content. Cheese produced with an equal proportion of buffalo and goat milk acquired the highest scores for texture, flavor and overall acceptability. Rheological measurements depicted that goat milk contributed to cohesiveness and hardness, whereas buffalo milk enhanced softness and meltability; however, storage increases the meltability and decreases cohesiveness. Further, the studies revealed that storage significantly influenced pH, acidity and nutritional characteristics of cheese samples. Cheese FAME showed that source of milk is the major contributor to variation; however, during storage, the value of short-chain fatty acids increases. The current study enlightens the potential of blending buffalo and goat milk for the manufacturing of high-quality Coalho cheese, which not only addresses the need for improving the milk utilization but is also vital for value addition prospects. These findings signify the importance of cheese formulations and the sustainable production of cheese from locally available sources. Further research for large-scale production and utilization of other sources of milk could be helpful for broaden the scope for the production of such products.